Role of mass media in combating drug-related crime - Yurtayeva, K. V.; Юртаєва, К. В.; Hladkova, Ye. O.; Гладкова, Є. О.; Shcherbakova, A. K.; Щербакова, А. К. (Baltic Journal of Economic Studies. – 2018. – Volume 4. – Number 3. – P. 366-371, 2018)
У статті розглянуто роль засобів масової інформації у протидії наркозлочинності, можливості взаємодії з ними поліції у даній сфері, а також проблеми, що виникають в рамках такої взаємодії в Україні. Зроблено висновок про важливість, передусім, превентивних заходів, направлених на обмеження споживання наркотичних речовин та ключову роль засобів масової інформації у цій діяльності, передусім через організацію спільних з поліцією та іншими органами державної влади інформаційних кампаній.

The purpose of the paper is to examine role of mass media in combatting drug addiction and drug related crimes, together with the opportunities of cooperation between the police and the mass media in combatting drug-related crimes and main problems arising from such cooperation. Results of the study allows us to draw several conclusions. Firstly, we underscore that there is a significant increase in drug consumption, especially among minors and youths. Under these circumstances, prevention-oriented approach to combatting drug related crimes gains special significance. Secondly, role of the mass media in shaping public perceptions of certain issues, including drugs, makes them a necessary partner for the law enforcement agencies in deterring spread of drug consumption. Thirdly, there are significant problems arising from the fundamentally different interests of the mass media and the police, which requires the latter to seek ways to align their activities. Still, we see cooperation as the only way to succeed, as administrative measures, such as censorship, will be largely counterproductive in the age of high availability of the information. Practical implications of the study lie in the recommendations for the activities of the police aimed at ensuring efficient cooperation with the mass media in organizing informational campaigns, promoting healthy lifestyle and discouraging drug consumption. We stress upon necessity of the well-planned campaign, including not only careful preparation of the information, but also selection of the most efficient channels of dissemination and setting up of the feedback in order to objectively appraise their results and to allow a certain level of flexibility in adapting and adjusting these campaigns to the circumstances. We also underscore importance of careful selection of the partners in mass media, so that both sides of the partnership have a deep understanding of the issue they are working with. Lastly, we investigate features of the information campaigns on the local level. Value/originality. The paper provides practical advices for setting up an informational campaign aimed at promoting healthy lifestyle and discouraging drug usage. Additionally, it provides basis for the further research of the issues of police-mass media cooperation, in counteracting drug-related crimes in particular and in prevention of antisocial and criminal behavior in general.

В статье рассмотрена роль средств массовой информации в противодействии наркопреступности, возможности взаимодействия с ними полиции в данной сфере, а также проблемы, возникающие в рамках такого взаимодействия в Украине. Сделан вывод о важности, прежде всего, превентивных мер, направленных на ограничение потребления наркотических веществ и ключевой роли средств массовой информации в этой деятельности, в первую очередь посредством организации совместных с полицией и другими органами государственной власти информационных кампаний.
Роль мас-медіа у протидії наркозлочинності
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u zarubizhnomu vydanni; police; mass media; information campaigns; drug-related crimes; drug consumption; drugs; полиция; средства массовой информации; информационные кампании; наркопреступность; употребление наркотиков; наркотики; поліція; засоби масової інформації; інформаційні кампанії; наркозлочинність; споживання наркотиків; publikatsii u WoS